Differential Efficacy of Anti-VEGF Antibodies Based on Sex and Race in a Diverse Cohort of Advanced Nonsquamous Non–Small Cell Lung Cancer. (January 2020) - Sukrithan, Vineeth; Barbaro, Alexander; Chergui, Adel; Ko, Brian; Lin, Juan; Cheng, Haiying; Goel, Sanjay
Abstract : Objectives: Bevacizumab with chemotherapy improved overall survival (OS) in the E4599 trial in metastatic nonsquamous non–small cell lung cancer (NS-NSCLC). A meta-analysis demonstrated an OS benefit with bevacizumab only in a subset of nonwhite patients. We explored the efficacy of antivascular endothelial growth factor antibodies (AVA) in a diverse cohort. Materials and Methods: Patients with advanced (stage IIIB/IV, American Joint Committee Cancer 7th edition) recurrent or metastatic NS-NSCLC diagnosed January 2006 to December 2017 at a single medical center were included. Survival analysis was performed with log-rank testing of the Kaplan-Meier estimator. Univariate models were constructed, and significant variables, age, sex, race were incorporated into a multivariate Cox proportional hazard model. Data analysis was performed on SAS. Results: A total of 171 patients, 80 were treated with AVA and 91 were untreated. Median age: 63 years, 55% females, 19% non-Hispanic whites, 44% blacks and 32% Hispanic whites; median 40 pack-years of smoking; 11.7% had sensitizing epidermal growth factor receptor mutations. Patients who received AVA had a survival benefit (26.6 vs. 19 mo, P =0.025). Adjusting for age, sex, race/ethnicity, epidermal growth factor receptor mutations, Eastern Cooperative Oncology Group performance status and number of metastases; AVA therapy was associated with improved OS (adjusted hazard ratio=0.62; P =0.049). In a subgroup analysis, females had survival benefit with AVA (median survival: 29.1 vs. 14.2 mo, log-rank P =0.02) which was significant in the adjusted model (adjusted hazard ratio=0.52; P =0.049). Conclusions: In a diverse cohort of patients with advanced NS-NSCLC, a survival benefit was confirmed with AVA. The greatest magnitude of benefit was in blacks and non-Hispanic whites. A significant survival benefit was limited to female patients.